The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/pc.23332
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity behavior of epoxy matrix nanocomposites with simultaneous dispersion of carbon nanotubes and clays

Abstract: In this work, nanocomposites with simultaneous dispersion of multiwalled carbon nanotubes (MWCNT) and montmorillonite clays in an epoxy matrix were prepared by in situ polymerization. A high energy sonication was employed as the dispersion method, without the aid of solvents in the process. The simultaneous dispersion of clays with carbon nanotubes (CNT) in different polymeric matrices has shown a synergic potential of increasing mechanical properties and electrical conductivity. Two different montmorillonite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Experimental works with nanoclays in epoxy showed that for these systems the intercalated state is the probably the best option to improve K Ic . There are other experimental works that showed that a mixture of clays (two‐dimensional [2D] material) with CNTs (one‐dimensional [1D] material) can assist the formation of a percolated network of CNTs . In this work, we tried to combine a 2D and 1D of fullerenes (graphenes and CNTs) expecting a better dispersion through the material and also to obtain synergy between two nanofillers with promising results for toughening when employed isolated in the literature for brittle polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental works with nanoclays in epoxy showed that for these systems the intercalated state is the probably the best option to improve K Ic . There are other experimental works that showed that a mixture of clays (two‐dimensional [2D] material) with CNTs (one‐dimensional [1D] material) can assist the formation of a percolated network of CNTs . In this work, we tried to combine a 2D and 1D of fullerenes (graphenes and CNTs) expecting a better dispersion through the material and also to obtain synergy between two nanofillers with promising results for toughening when employed isolated in the literature for brittle polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it can immobilize, interrupt or even ramify the crack propagation , resulting in a higher absorption of fracture energy, which leads to an increase in fracture toughness . Despite that, experimental evidence indicates that, for nanoclays in epoxy matrices, the intercalated state is more efficient for the absorption of fracture energy than a homogeneous exfoliated state .…”
Section: Introductionmentioning
confidence: 99%
“…Sene et al. 24 also found an increase in electrical conductivity at low frequencies (percolation network) with pristine MWCNT 0.25 wt.% (∼0.15 vol.%) reaching values for electrical conductivity in the order of 10 −7 S/m. This electrical conduction happens by the displacement of the resonant π electrons of benzene rings through the concentric tubes.…”
Section: Resultsmentioning
confidence: 92%